A STUDY ON HYPOGLYCAEMIC HEALTH CARE FUNCTION OF STIGMA MAYDIS POLYSACCHARIDES - Zhang, Yan; Wang, Jing-bo; Wang, Liang; Zhen, Li-ying; Zhu, Quang-qing; Chen, Xiao-wen (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to study the therapeutic effect of Stigma maydis polysaccharides in diabetic mice. Mouse models of types 1 and 2 diabetes were established. The body weight, food intake, water intake as well as blood sugar level and glucose tolerance of mice were measured. Stigma maydis polysaccharides can improve the symptoms of weight loss and polydipsia in diabetic mice, and had an obvious antagonistic effect on alloxan-induced hyperglycaemia. The glucose tolerance test also showed that the Stigma maydis polysaccharides had very good effects on suppression and prevention of acute hyperglycaemia. Stigma maydis polysaccharides have some improvement effect on alloxan-induced types 1 and 2 diabetes.